Risk factors for conversion in laparoscopic and robotic rectal cancer surgery. Issue 5 (24th January 2020) - Crippa, J; Grass, F; Achilli, P; Mathis, K L; Kelley, S R; Merchea, A; Colibaseanu, D T; Larson, D W
Abstract: Background: The aim of this study was to review risk factors for conversion in a cohort of patients with rectal cancer undergoing minimally invasive abdominal surgery. Methods: A retrospective analysis was performed of consecutive patients operated on from February 2005 to April 2018. Adult patients undergoing low anterior resection or abdominoperineal resection for primary rectal adenocarcinoma by a minimally invasive approach were included. Exclusion criteria were lack of research authorization, stage IV or recurrent rectal cancer, and emergency surgery. Risk factors for conversion were investigated using logistic regression. A subgroup analysis of obese patients (BMI 30 kg/m 2 or more) was performed. Results: A total of 600 patients were included in the analysis. The overall conversion rate was 9·2 per cent. Multivariable analysis showed a 72 per cent lower risk of conversion when patients had robotic surgery (odds ratio (OR) 0·28, 95 per cent c.i. 0·15 to 0·52). Obese patients experienced a threefold higher risk of conversion compared with non-obese patients (47 versus 24·4 per cent respectively; P < 0·001). Robotic surgery was associated with a reduced risk of conversion in obese patients (OR 0·22, 0·07 to 0·71). Conclusion: Robotic surgery was associated with a lower risk of conversion in patients undergoing minimally invasive rectal cancer surgery, in both obese and non-obese patients. Graphical Abstract: The aim of this study was to investigate the risk factors for conversion in patients having minimally invasive surgery for rectal cancer. Robotic surgery was associated with a decreased risk of conversion compared with a laparoscopic approach in a high-volume centre with long-standing experience. Robt reduces conversion